Perception of community and hospital pharmacists in Metro Manila of their overall preparedness for the preceptor role - Delos Santos, Jebb Patrick M.; Tagorda, John Ezekiel P.,​​; Tan, Deborah Lorraine Y. (2017)
An internship program is a partnership between a school and an internship site. A preceptor has key responsibility in achieving the objectives of an internship program by facilitating activities and supervising the interns during program. This study aimed to evaluate community and hospital pharmacists' perception of their overall preparedness for the preceptor role. It employed descriptive, correlational design using survey questionnaire as the method of data collection. This study was conducted in Metro Manila with nine internship sites included, one from the community and eight from the hospital settings, and 175 responses analyzed using logistic regression analysis. In the community setting, perception of support was significantly related to knowledge and level of preparedness, and perception of teaching competency to experience and interest. In the hospital setting, among the independent variables, perception of benefits and rewards, support, ability to provide pharmaceutical care, and teaching competency, and pharmaceutical practice are significant predictors of all the dependent variables. In addition, the prescription volume was also found to be significantly related to motivation, and number of CPD programs attended to level of preparedness. Overall, the pharmacists had a positive perception of overall preparedness for the preceptor role.